Tracer la question de la croissance dans le capitalisme cybernétique - Jacob BOIVIN (Tic & Société)
This article questions the compatibility of current forms of digitalization with injunctions to make an ecological transition by juxtaposing the current of degrowth and the political economy of digital technology. Framed through the mutations of capitalism brought about by the cybernetic revolution, growth is expressed on three levels: as an ideology, a social process, and a material process. What emerges is a joint, dynamic relationship between the imperative of growth and the imperative of digitalization, which translates into a logic of algorithmic governmentality and renewed extractivism. This article therefore offers several anchor points for the critical analysis of the growth imperative in the context of contemporary digitalization.